Cavitation observations and noise measurements of horizontal axis tidal turbines with biomimetic blade leading-edge designs. (15th July 2016) - Shi, Weichao; Atlar, Mehmet; Rosli, Roslynna; Aktas, Batuhan; Norman, Rosemary
Abstract: This paper focuses on the study of cavitation and underwater noise performance of a biomimetically improved horizontal axis tidal turbine (HATT) with a leading edge design inspired by the tubercles on the pectoral fins of humpback whales. Systematic model tests were recently conducted and details of this test campaign together with the findings are summarised in the paper. Several full-scale tidal turbine application cases were studied to understand the full-scale operating conditions considering the characteristics of varied kinds of tidal energy devices, the varying wave height and the flood/ebb tide. A systematic test regime was then designed and conducted. A set of tidal turbines with different leading-edge profiles was manufactured and tested under different loading and hence cavitation conditions. During the tests, cavitation was observed and underwater noise level was measured in comparison with the cavitation and noise performance of a counterpart HATT without tubercles. The tested turbines displayed two main types of cavitation patterns independent of the tubercles. These were steady tip vortex cavitation and relatively intermittent cloud cavitation with a misty appearance. The leading-edge tubercles triggered the cavitation onset earlier for the tidal turbine but constrained the cavitation region to the trough between tubercles with a lesser extent on the blades. The noise performance was strongly related to the blade cavitation hence it was influenced by the leading-edge tubercles. While the turbine was working under the non-cavitating conditions the total noise level was similar to the background noise level. With the increase of the tip speed ratio the noise level was increased, while increasing blade pitch angle reduced the noise level due to lower blade loading. Cavitation inception and noise diagrams are provided as a database for future studies. Highlights: A biomimetic leading-edge tubercle design is applied on a tidal turbine model. A systematic cavitation and noise test has been conducted in a cavitation tunnel. Tubercles trigger the cavitation onset earlier but control the cavitation area. Noise is strongly related to the cavitation and influenced by the tubercles. Cavitation and noise diagrams are provided as a benchmark data for future studies.